2020
DOI: 10.3390/jcm9041066
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Subthreshold Micropulse Yellow Laser as an Alternative Option for the Treatment of Refractory Postoperative Cystoid Macular Edema

Abstract: Background: To evaluate the efficacy and the safety of subthreshold micropulse yellow laser (SMYL) in the treatment of chronic postoperative cystoid macular edema (PCME), which is refractory to standard therapies. Methods: A retrospective chart review of ten eyes of ten patients affected by refractory PCME who underwent SMYL was performed. Five PCME cases were subsequent to uncomplicated cataract surgery (CS), two cases to complicated CS (CCS) with posterior capsule rupture and three cases occurred after retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Verdina et al retrospectively included ten eyes of ten patients with refractory PCME to standard treatments, namely NSAI eyedrops, topical steroids, oral indomethacin, sub-Tenon triamcinolone injections and dexamethasone intravitreal implant [ 125 , 126 ]. All underwent YSML and were followed up for 6 months.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Verdina et al retrospectively included ten eyes of ten patients with refractory PCME to standard treatments, namely NSAI eyedrops, topical steroids, oral indomethacin, sub-Tenon triamcinolone injections and dexamethasone intravitreal implant [ 125 , 126 ]. All underwent YSML and were followed up for 6 months.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Beneficial results on the use of SMYL in the treatment of DME have been already reported by several authors in the literature ( Bucolo et al, 2015 ; Verdina et al, 2020 ; Donati et al, 2021 ). Vujosevic et al showed a significant improvement of BCVA from 69.7 ± 12.0 to 74.3 ± 9.5 ETDRS letters 6 months after treatment, although retinal thickness did not change during the follow-up ( Vujosevic et al, 2020 ).…”
Section: Discussionmentioning
confidence: 80%
“…Two hundred milliseconds of exposure and 4 grids (7 × 7) with confluent spots of 200 μm (0.00 spacing), including the foveal center were used. The setting, including the spot size, lens, and duration remained the same as it was in the test spot ( Verdina et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, Verdina et al published the first results of the treatment of refractory postoperative CME with subthreshold micropulse yellow laser in 10 eyes of 10 patients [ 46 ]. Five eyes of five patients had Irvine–Gass syndrome.…”
Section: Resultsmentioning
confidence: 99%